ECONOMIC EMPOWERMENT STRATEGY MODEL FOR COASTAL WOMEN ON THE BASIS OF BLUE ECONOMY AND LOCAL POTENTIAL IN SURABAYA - Rahmiyati, Nekky -; Rachmawati, Titiek (Universitas Dharma Wacana, 2023)
This study aimed to determine the role of coastal women in improving the economy of fishermen family, the role of coastal women in implementing blue economy, and the right empowerment strategy model for coastal women. The type of this research was quantitative, the number of samples was 50 and the sampling technique was purpose sampling. This study used SWOT analysis. This research found that coastal women have not played a role in the application of the blue economy, obstacles in the application of the blue economy include: from the side of fishermen (producers) there were still many fishermen's wives who have low knowledge, especially about the blue economy. Practices that were not environmentally friendly, for example the use of plastic in every activity, throwing garbage / waste into the sea / drying the fish on the highway, this showed a low level of understanding the minimize waste, which means that in the production process must produce clean products (clean production) with no waste (zero waste). The role of coastal women in utilizing local potential at tourist beaches was still not optimal because KPPI members did not have skills, especially no innovation and no product variations from fishermen's catches, and weak marketing strategies. The results of the SWOT analysis showed that the main strategy generated was the SO strategy with the highest score of 3.9 in position 1, namely using strengths to seize and take advantage of the maximum opportunities